Characterization of Lard Profile from Different Geographical Regions of Husbandries and Body Parts of Pig using FTIR Technique Combined with Chemometrics - N.A.M Salleh; N. Yahaya; D. Rosli,; M.F. Azizan; Bohari M Yamin; M.S. Hassan (IJASEIT, 2024)
Indexed by Scopus/ERA